Isoperla prokopovi, a new presumedly parthenogenetic stonefly from Crimea (Plecoptera, Perlodidae) - Zhiltzova, Lidia A. (Illiesia, 2012)
Isoperla prokopovi sp. n. from Crimea is described from females, larvae, and eggs. Males or male larvae were not found, despite concerted efforts. The species is therefore believed to be parthenogenetic. The life cycle appears to be univoltine, possibly with a long egg diapause. The thick egg chorion differs from other Perloidea in that it disintegrates in KOH. Isoperla prokopovi is an isolated species without apparent close relatives among the West Palaearctic Isoperla spp.
Keywords: entomology; Perlodidae; Plecoptera; Isoperla prokopovi; taxonomy; parthenogenesis; Crimea; new species; life cycle; Ukraine